Clinicopathological characterization of 317 odontomas: a collaborative Latin American study - Tenório, Jefferson da Rocha; Ventura, José Victor Lemos; Andrade, Marcela Lopes de; Contreiras, João Pedro Silva; Binimeliz, Marina; Cavalcante, Israel Leal; Netto, Juliana de Noronha Santos; Guedes, Fábio Ribeiro; Villarroel-Dorrego, Mariana; Peña-Vega, Claudia Patricia; Rodríguez-Mora, Juan Pablo; Cordero-Torres, Karina; et al. (Journal of Oral Diagnosis, 2025)
Objective: The present study aimed to evaluate the clinicopathological features of odontomas diagnosed at five oral diagnostic services across Latin America. Methods: A retrospective cross-sectional study (2000–2024) was conducted, including institutions from five Latin American countries (Brazil, Venezuela, Colombia, Chile, and Costa Rica). Data from 317 odontoma cases were analyzed, including patient sex, age, anatomical site, clinicopathological subtype, and the presence of associated odontogenic lesions. Results: The median age at diagnosis was 16 years (range: 4–83 years), with a slight male predominance (52.7%, n=167). The anterior maxilla was the most commonly affected site (39.9%). Compound odontomas represented the majority of cases (65.9%). Notably, 24 cases (8.7%) were associated with other odontogenic lesions, most frequently dentigerous cysts (6.6%, n=21). Conclusion: This multicenter study highlights that odontomas in a Latin American population predominantly affect the maxilla, are primarily diagnosed in younger individuals, and most commonly present as the compound subtype.